Bruised - Boteju, Tanya (Simon & Schuster BFYR, 2021)
Daya Wijesinghe sees a bruise as a mixture of comfort and control. Since her parents died in an accident Daya Wijesinghe survived, bruises have become a way to keep her pain on the surface of her skin so she doesn't need to deal with the ache deep in her heart. When chance brings her to a roller derby bout, Daya is hooked. Yes, the rules are confusing and the sport seems to require the kind of teamwork and human interaction Daya generally avoids, but the opportunities to bruise are countless. As her rough-and-tumble teammates and their fans push her limits in ways she never imagined, Daya realizes some big truths about love, loss, strength, and healing. -- adapted from jacket